2021
DOI: 10.3390/ijms222011283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Inhibition Activity Study of Triazinyl-Substituted Amino(alkyl)-benzenesulfonamide Conjugates with Polar and Hydrophobic Amino Acids as Inhibitors of Human Carbonic Anhydrases I, II, IV, IX, and XII

Abstract: Primary sulfonamide derivatives with various heterocycles represent the most widespread group of potential human carbonic anhydrase (hCA) inhibitors with high affinity and selectivity towards specific isozymes from the hCA family. In this work, new 4-aminomethyl- and aminoethyl-benzenesulfonamide derivatives with 1,3,5-triazine disubstituted with a pair of identical amino acids, possessing a polar (Ser, Thr, Asn, Gln) and non-polar (Ala, Tyr, Trp) side chain, have been synthesized. The optimized synthetic, pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Synthesized compounds were also subjected to molecular docking studies and it was observed that compound 184 (R 1 = Trp) showed binding energy −219.74, −156.70, and −225.14 kJ/mol for hCA II, hCA IX, and hCA XII, respectively, and proved to be a good inhibitor [39] (Scheme 20). | 13 of 208 Newly synthesized compounds were tested for their inhibitory activity against hCA I, II, IX, XII by taking AAZ as standard drug by using stopped flow CO 2 hydration assay and it was observed that compound 204a (sulfonamide moiety) showed potent inhibitory activity against hCA IX and XII with K i values of 11.7 and 9.8 nM, respectively, and compound 205a (sulfonamide moiety) showed activity against hCA IX and XII with K i values of 29.7 and 45.5 nM, respectively.…”
Section: S C H E M E 17 Synthesis Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesized compounds were also subjected to molecular docking studies and it was observed that compound 184 (R 1 = Trp) showed binding energy −219.74, −156.70, and −225.14 kJ/mol for hCA II, hCA IX, and hCA XII, respectively, and proved to be a good inhibitor [39] (Scheme 20). | 13 of 208 Newly synthesized compounds were tested for their inhibitory activity against hCA I, II, IX, XII by taking AAZ as standard drug by using stopped flow CO 2 hydration assay and it was observed that compound 204a (sulfonamide moiety) showed potent inhibitory activity against hCA IX and XII with K i values of 11.7 and 9.8 nM, respectively, and compound 205a (sulfonamide moiety) showed activity against hCA IX and XII with K i values of 29.7 and 45.5 nM, respectively.…”
Section: S C H E M E 17 Synthesis Ofmentioning
confidence: 99%
“…Synthesized compounds were also subjected to molecular docking studies and it was observed that compound 184 (R 1 = Trp) showed binding energy −219.74, −156.70, and −225.14 kJ/mol for hCA II, hCA IX, and hCA XII, respectively, and proved to be a good inhibitor [ 39 ] (Scheme 20).…”
Section: Chemistry Of Heterocycles As Ca Inhibitorsmentioning
confidence: 99%